Impact of waist-hip-ratio and body-mass-index on hormonal and metabolic parameters in young, obese women - Hollmann, Michaela; Runnebaum, Benno; Gerhard, Ingrid (International journal of obesity and related metabolic disorders, 1997)
BACKGROUND: To investigate the impact of predominantly upper body fat localisation on the hormonal and metabolic profile in obese, infertile women. DESIGN: Prospective observational study of premenopausal women with obesity, infertility and menstrual dysfunction. SETTING: Department of Endocrinology and Reproduction of the University Hospital of Obstetrics and Gynaecology of Heidelberg. SUBJECTS: Eighteen women with android type obesity (waist-hip-ratio=WHR>0.85, group 1) and 22 women with gynoid type obesity (WHR≤0.85, group 2) in a group of 58 premenopausal obese women (median age 28 y) with infertility. Twenty-nine women took part in a weight reducing program lasting 32±14 (mean±s.d.) weeks. MEASUREMENTS: BMI, WHR and blood pressure. Plasma lipids and liver enzymes. Blood glucose, insulin, C-peptide and different steroid and pituitary hormones during oral glucose loading. RESULTS: In the total group of 58 obese women, WHR was directly correlated to plasma triglycerides, AST, ALT and cholesterol/HDL-cholesterol-ratio. WHR correlated inversely with HDL-cholesterol. Insulin resistance was greater with increasing WHR. Systolic blood pressure, glucose, insulin, C-peptide, triglycerides, cholesterol/HDL-cholesterol-ratio, aspartate (AST) and alanine aminotransferase (ALT) were significantly greater in group 1. Group 2 had greater HDL-cholesterol levels. One subject in group 1, five women in group 2 conceived spontaneously after weight reduction. CONCLUSIONS: Determination of the WHR is a simple measurement to identify obese patients who are at a greater risk of developing the metabolic syndrome. WHR is important in preventive medicine, as typical metabolic profiles are already present in young women before clinical manifestation. Women with android obesity seem to be more prone to develop menstrual irregularity and infertility. The hyperinsulinaemia may be the pathway.
Gesehen am 03.04.2025